2014
DOI: 10.1002/celc.201402142
|View full text |Cite
|
Sign up to set email alerts
|

Insights on Hybrid Glucose Biofuel Cells Based on Bilirubin Oxidase Cathode and Gold‐Based Anode Nanomaterials

Abstract: International audienceWe report a straightforward design for a hybrid glucose biofuel cell (h-GBFC) operating at pH7.4 with 10mM glucose at 37 degrees C. Homemade electrospun carbon nanofibers were used as electrode support. Clean and highly active gold-based nanomaterials (3-6nm) were synthesized for glucose electrooxidation. Enhanced catalytic activity toward glucose oxidation has been highlighted. Bilirubin oxidase enzyme was used to catalyze the oxygen reduction reaction. The constructed h-GBFCs exhibit an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
40
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 25 publications
(42 citation statements)
references
References 102 publications
(131 reference statements)
2
40
0
Order By: Relevance
“…Thus, the partial or total substitution of Cl − by bromide anions must accentuate steric hindrance around the metal cation, which will further play a crucial role during the seed's growth. This advanced method has been successfully used to synthesize Au-based nanocatalysts for glucose electro-oxidation [38,57], Pd-based electrocatalysts for glycerol electro-oxidation [36,37,101] and hybrid/abiotic electrodes for biofuel cell application [102,103]. This convenient and straightforward synthesis approach is an environmentally friendly method and is based on the use of bromide ion as a capping agent, the major gate in the BAE process.…”
Section: Bromide Anion Exchange (Bae) Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Thus, the partial or total substitution of Cl − by bromide anions must accentuate steric hindrance around the metal cation, which will further play a crucial role during the seed's growth. This advanced method has been successfully used to synthesize Au-based nanocatalysts for glucose electro-oxidation [38,57], Pd-based electrocatalysts for glycerol electro-oxidation [36,37,101] and hybrid/abiotic electrodes for biofuel cell application [102,103]. This convenient and straightforward synthesis approach is an environmentally friendly method and is based on the use of bromide ion as a capping agent, the major gate in the BAE process.…”
Section: Bromide Anion Exchange (Bae) Methodsmentioning
confidence: 99%
“…They also found that Pt/C and Pt/KB exhibited a highly improved specific electrochemical surface area (SECSA). It is worthy of note that all catalysts were prepared with a high chemical synthesis yield (ϖ > 90 %), defined as the percentage of the ratio between the experimental mass and the theoretical one based on the initial reactor mixture [102,103]. It should be emphasized that it is the first time that such a synthesis yield has been reported.…”
Section: Bromide Anion Exchange (Bae) Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…12,25 We reported the use of "Bromide Anion Exchange" (BAE) method, [29][30][31] a surfactant-free approach, to develop a line-up of Au-Pd-Pt nanocatalysts able to oxidize efficiently glucose at low electrode potentials at various pHs. [32][33][34] It was also shown that monometallic Au enables a selective oxidation of a range of carbohydrates by their anomeric position and even in a cogeneration fuel cell; 13,35 however, it was postulated that the selectivity remained limited to Au that exhibits remarkable catalytic activity [36][37][38] toward aldehydes and hemiacetals oxidation. Herein, we examine the extended analysis on Au 100-x M x (M = Pd, Pt) catalysts by coupling electrochemical techniques with spectroscopic and chromatographic methods to unravel the outstanding ability of these electrocatalysts, enabling the acquisition of clear and precise information on the electrocatalytic reaction.…”
Section: H426mentioning
confidence: 99%
“…In contrast, electrospinning is a simple and versatile technique to fabricate 1D carbon nanomaterials without need of complex set-up, which offers a promising route for large-scale production of nanofibers. 15 The electrospun CNFs have been applied to electrochemistry as supercapacitors, 16 electrodes for Li-ion batteries, 17 biofuel cell, 18 and catalyst supports, 19 but few investigations were focused on their ORR properties in fuel cell. 15b, 20 In spite of their high nitrogen contents, the as-electrospun nitrogen-doped CNFs showed low activity for ORR due to low surface areas because most nitrogen-containing groups are buried in carbon matrix, 21 thus which are inaccessible to the reactants.…”
Section: Introductionmentioning
confidence: 99%